2018
DOI: 10.1155/2018/1067853
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pravastatin on Type 1 Diabetic Rat Heart with or without Blood Glycemic Control

Abstract: Although statins have been suggested to attenuate the progression of diabetic cardiomyopathy, its effect without glycemic control remains unclear. Therefore, we evaluated the effect of pravastatin on diabetic rat hearts according to glycemic control. Rats were randomly divided into five groups: control (C), diabetes (D), diabetes with insulin (I), diabetes with pravastatin (P), and diabetes with insulin and pravastatin (IP). Eight weeks after allocated treatments, the heart was extracted and analyzed following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 30 publications
3
12
0
Order By: Relevance
“…In a model of experimental atherosclerosis in rabbits, atorvastatin increased ACE2 protein levels in heart and kidneys, compared to untreated atherosclerotic animals (Dong et al, 2008; South et al, 2020). Similar results were observed using rosuvastatin or pravastatin in rat vascular balloon injury or diabetes (Li et al, 2013; Min et al, 2018). However, in those studies, ACE2 levels were decreased in injured tissues compared to healthy groups, and therefore, ACE2 up‐regulation induced by statins is only described under disease situations.…”
Section: Statin Effects In the Key Sars‐cov‐2 Entry Pathways: Ace2 Ansupporting
confidence: 77%
“…In a model of experimental atherosclerosis in rabbits, atorvastatin increased ACE2 protein levels in heart and kidneys, compared to untreated atherosclerotic animals (Dong et al, 2008; South et al, 2020). Similar results were observed using rosuvastatin or pravastatin in rat vascular balloon injury or diabetes (Li et al, 2013; Min et al, 2018). However, in those studies, ACE2 levels were decreased in injured tissues compared to healthy groups, and therefore, ACE2 up‐regulation induced by statins is only described under disease situations.…”
Section: Statin Effects In the Key Sars‐cov‐2 Entry Pathways: Ace2 Ansupporting
confidence: 77%
“…Fluvastatin reduces diabetic cardiac fibrosis, improves cardiac function and enhances ACE2 expression in glucose-controlled diabetic rats (Shin et al, 2017). Similar findings with cardiac ACE2 preservation have been observed for pravastatin (Min et al, 2018). Likewise, atorvastatin inhibits TNF-α mediated suppression of ACE2 and upregulation of ACE in cultured vascular smooth muscle cells.…”
Section: Lipid Lowering Drugs-supporting
confidence: 73%
“…These effects were attributed to the recovered ratio of ACE/ACE2 rather than an increased level of ACE2 [ 78 ]. Further studies in diabetic rats confirmed that statin administration increased ACE2 mRNA in cardiac tissue from insulin-controlled groups, although this was not accompanied by significant effects on cardiac fibrosis and reactive oxygen species generation [ 79 , 80 ]. In our current report, 33% of COVID19 cases that used statins were diabetic.…”
Section: Discussionmentioning
confidence: 99%